2021
DOI: 10.1111/ijpo.12779
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity behaviour and screen time in Dutch children during the COVID‐19 pandemic: Pre‐, during‐ and post‐school closures

Abstract: Summary Background Measures during the COVID‐19 pandemic, including the closure of schools and sports facilities, may have lasting impact on the physical activity (PA) of children that persists for a long time. Objective To investigate the effect of COVID‐19 measures on screen time and PA in Dutch children pre‐, during‐ and post‐school closures. Methods In cohort A (n = 102, 10.5 ± 3.6 years, 42.4% boys), data on PA and screen time during the lockdown were collected using a questionnaire. In cohort B (n = 131,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
121
4
24

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(198 citation statements)
references
References 26 publications
18
121
4
24
Order By: Relevance
“…We present a novel qualitative contribution to existing quantitative data exploring COVID-19-related changes in children’s movement behaviours, include the perceptions of children regarding their pandemic experiences, and provide data from families in non-urban contexts. Online self-reported surveys have identified a general decrease in physical activity during the pandemic, including a reduction in the number of children meeting physical activity guidelines and a specific reduction in some domains of physical activity including outside play and sport [ 16 ], even after school and sports facilities re-opened [ 21 ]. Findings from our current work support these overall trends and provide a nuanced description of how families are coping with COVID-19 restrictions, reflecting daily anxieties related to disease transmission and ongoing adaptations to play routines to maintain friendship networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We present a novel qualitative contribution to existing quantitative data exploring COVID-19-related changes in children’s movement behaviours, include the perceptions of children regarding their pandemic experiences, and provide data from families in non-urban contexts. Online self-reported surveys have identified a general decrease in physical activity during the pandemic, including a reduction in the number of children meeting physical activity guidelines and a specific reduction in some domains of physical activity including outside play and sport [ 16 ], even after school and sports facilities re-opened [ 21 ]. Findings from our current work support these overall trends and provide a nuanced description of how families are coping with COVID-19 restrictions, reflecting daily anxieties related to disease transmission and ongoing adaptations to play routines to maintain friendship networks.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with an increase in physical activity during the pandemic were family encouragement, parental engagement, and dog ownership [ 16 ]. Variation in changes to movement behaviours during the pandemic has been attributed to regional difference in public health policies including school, facility and park closures [ 21 , 22 ], neighbourhood environments such as population density and proximity to major roads [ 20 ], and family-level factors such as living in a single-family versus multi-family dwelling [ 16 , 23 ]. Previous qualitative work conducted in urban areas has identified parental stress, uncertainty in navigating pandemic restrictions, and reduced access to green spaces as factors negatively impacting children’s movement behaviours during COVID-19 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once the increased risk of infection in children is recognized by policy makers and society, it is likely that there will be prolonged school closures in the Western Pacific region, the negative impact of which cannot be ignored [ 15 ]. Several studies reported that during the school closures, the time spent on physical activity decreased but sedentary time increased [ 16 , 17 ], which may cause overweight in children [ 18 ]. In addition, school closure result in undernutrition in those children who depend on free meals in schools [ 19 ].…”
Section: Negative Effects Of Prolonged School Closuresmentioning
confidence: 99%
“…During the school closure period, i.e., the home-based learning period, children’s sleeping time became longer than that before school closure, bedtime was later, and wake-up time was much later than that before school closure [ 17 ], indicating that children’s life rhythm has been disturbed. Moreover, increased screen time due to home-based learning using internet materials was thought to have had some impact as well [ 16 , 20 ], and even non-academic screen time also increased, which might affect children’s sleep [ 17 ]. Furthermore, children’s mental health has been affected, with increasing reports of behavioral problems, anxiety, depression, and stress [ 21 , 22 ].…”
Section: Negative Effects Of Prolonged School Closuresmentioning
confidence: 99%
“…Therefore, developing good goals and attitudes toward PA is a vital step for one to stay healthy. This is especially important in times of the current COVID-19 pandemic which has severely impact the levels of PA among children in reducing their health-related quality of life ( Ten Velde et al, 2021 ). Inevitably, a better understanding of the primary school students’ goal and attitudes would provide invaluable feedback to help the PE educators plan, strategize and make better teaching-related choices according to the students’ learning motivation and self-management skills in PA participation during the pandemic.…”
Section: Introductionmentioning
confidence: 99%